Scribble and α-Catenin cooperatively regulate epithelial homeostasis and growth - Huang, Yunxian; Gui, Jinghua; Myllymäki, Satu-Marja; Roy, Kallol; Tõnissoo, Tambet; Mikkola, Marja L.; Shimmi, Osamu (Frontiers in Cell and Developmental Biology, 2022)
Epithelial homeostasis is an emergent property of both physical and biochemical signals emanating from neighboring cells and across tissue. A recent study reveals that Scribble, an apico-basal polarity determinant, cooperates with α-Catenin, an adherens junction component, to regulate tissue homeostasis in the Drosophila wing imaginal disc. However, it remains to be addressed whether similar mechanisms are utilized in vertebrates. In this study, we first address how α-Catenin cooperates with Scribble to regulate epithelial homeostasis and growth in mammalian cells. Our data show that α-Catenin and Scribble interact physically in mammalian cells. We then found that both α-Catenin and Scribble are required for regulating nuclear translocation of YAP, an effector of the Hippo signaling pathway. Furthermore, ectopic Scribble suffices to suppress YAP in an α-Catenin-dependent manner. Then, to test our hypothesis that Scribble amounts impact epithelial growth, we use the Drosophila wing imaginal disc. We show that Scribble expression is complementary to Yorkie signal, the Drosophila ortholog of YAP. Ectopic expression of full-length Scribble or Scribble Leucine Rich Region (LRR):α-Catenin chimera sufficiently down-regulates Yorkie signal, leading to smaller wing size. Moreover, Scribble LRR:α-Catenin chimera rescues scribble mutant clones in the wing imaginal disc to maintain tissue homeostasis. Taken together, our studies suggest that the association of cell polarity component Scribble with α-Catenin plays a conserved role in epithelial homeostasis and growth.